Análise espacial da especialização agropecuária dos municípios mato-mrossenses : fatores econômicos, sociodemográficos e ambientais - Moi, Paula Cristina Pedroso (2018)
The major economic activities of the legal Amazon region are the vegetal extractivism, cattle farming, and agriculture. Mato Grosso is one of the Brazilian federative states that make up the southern part of this area, whose economy is primarily dependent on the agribusiness activity and in which the environmental and social impact of this uncontrolled expanded activity is not yet treated as an economically significant variable. It was used a critical literature with contemporary approaches as a theoretical basis for the interpretation of the regionalization process. In this sense, the objective is to analyze the joint spatial distribution of the specialization level within the agricultural activity of each municipality (QLagro) in the state of Mato Grosso, during the period 2005-2014 and explore possible associations with socio-demographic, economic and environmental aspects. First, through the locational quotient (QL) method, the productive specialization of each region of the State was measured. Starting from the analytical model, where the univariate exploratory analysis of the spatial data for the investigation of global spatial autocorrelation was performed, the level of specialization in the agricultural activity (QLagro), through the Moran I index, which measures the correlation between each one with its neighbors. In the bivariate analysis, the correlation between the variables distributed in three categories - socio-demographic, economic and environmental - was analyzed with the QLagro using the Pearson correlation coefficient (r). Thereafter, it was added to the spatial multiple regression analysis, the variables that obtained the highest significance in the calculation of the Pearson correlation coefficient. The results of the final spatial regression analysis model show the consumption of pesticides, taxes, the level of education of the person who runs the establishment (uneducated), and the Gini index with a significant inverse association related to the level of specialty in the agricultural activity (QLagro) of the municipalities belonging to Mato Grosso from 2005 to 2014 (p <0.05). In addition, the transport companies rate and the rural resident population rate were positively associated with QLagro (p <0.05). This research reveals the importance of analyzing the factors associated with the spatial groupings of the agricultural sector in the municipalities belonging to the Legal Amazon. The results bring important contributions to understanding the spatial, economic, sociodemographic and environmental aspects involved in this process of regional specialization that provided essential information for future planning aimed at a competitive development strategy geared to the less developed regions.